Fighters, antagonists, travel companions. Remarks on groups of anonymous young heroes in Homeric epic poetry (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The paper discusses examples of anonymous groups of young men in the Homeric epos and considers their literary function. Compared with the Iliad, such groups, especially the Suitors, in the Odyssey have a better-defined collective voice precisely as young men, as it is shown by the formulaic usage, and their key role is closely connected with their age
Keywords: Iliad; Homer; youth; “τις-speeches”; Odyssey; Suitors